The Book of Ruth and Blanche of Castile : women with a heart of men - Barṭal, Rut (Alexandros Press, 2023)
Although The Book of Ruth did not gain a remarkable status in the corps of the visual arts of the early centuries of the Christian era, it became a major theme in the works commissioned under the rule of the Capetian family in 13th-century France. It was Blanche of Castile who initiated the presentation of the Book of Ruth, assumingly, for two main reasons: As the Capetians considered themselves descendants of the Davidic dynasty and its legitimate heirs, it was only appropriate to manifest Ruth, the biblical heroine, the ancestor of King David. Furthermore, the exegesis of the Book of Ruth that emphasizes the dissemination of Christianity and the triumph of the Church over heresy and Judaism suited the Capetian political and religious ideology. Moreover, the presentation of the Book of Ruth on the stained windows in the Sainte Chapelle in Paris invokes the notion that the Book of Ruth also served as a typological representation of the Capetian royal family and the relations between its members. Ruth Bartal creates a fascinating analogy between the biblical figures of The Book of Ruth and The Capetian queens that were described as "Women with a heart of men" through examining four masterpieces of the 13th century: The Bibles moralisées, The Morgan Bible, The Saint Capelle and The Arsenal Bible. --